2021
DOI: 10.3389/fimmu.2021.642316
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience and Recent Advances in the Development of Listeria-Based Tumor Immunotherapies

Abstract: The promise of tumor immunotherapy to significantly improve survival in patients who are refractory to long-standing therapies, such as chemotherapy and radiation, is now being realized. While immune checkpoint inhibitors that target PD-1 and CTLA-4 are leading the charge in clinical efficacy, there are a number of other promising tumor immunotherapies in advanced development such as Listeria-based vaccines. Due to its unique life cycle and ability to induce robust CTL responses, attenuated strains of Listeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 140 publications
(222 reference statements)
0
28
0
Order By: Relevance
“…Firstly, the basal expression of genes modulating the innate immune response and regulating the cell cycle was assessed. Secondly, we evaluated this cell line’s interaction with two types of infectious stressors, which are currently studied as new anti-cancer therapies [ 31 ]. Moreover, we demonstrated that the CF33 cell line at different passages shows the same characteristics of gene expression as canine mammary carcinoma (CMC) [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the basal expression of genes modulating the innate immune response and regulating the cell cycle was assessed. Secondly, we evaluated this cell line’s interaction with two types of infectious stressors, which are currently studied as new anti-cancer therapies [ 31 ]. Moreover, we demonstrated that the CF33 cell line at different passages shows the same characteristics of gene expression as canine mammary carcinoma (CMC) [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We next asked if the functional TST subset present in mice with early lesions could be harnessed to stop tumor progression. Listeria monocytogenes (LM) is a gram-positive intracellular bacterium which induces strong CD4 and CD8 T cell responses 19 . Using an actA inlB deficient attenuated LM vaccination strain 20 , which has been used in human clinical trials for advanced cancers [21][22][23] , and engineered to express the TAG epitope I (LMTAG) 5 , we tested whether early vaccination of AST;Cre-ER T2 would protect mice from liver cancer progression.…”
Section: Vaccination Early During Tumorigenesis Halts Cancer Progressionmentioning
confidence: 99%
“…Attenuated strains of Listeria monocytogenes have been utilized as vaccine vectors targeting different tumors, especially human papillomavirus (HPV)-associated cancers, pancreatic cancer, and malignant pleural mesothelioma, improving the survival of patients ( 71 ). As for CRC, a personalized live-attenuated, double-deleted (pLADD) L. monocytogenes -based immunotherapy was designed for a phase 1 trial to analyze its safety (NCT03189030).…”
Section: Different Types Of Colorectal Cancer Vaccinesmentioning
confidence: 99%